Audit Fee, Audit Tenure, Auditor’s Reputation, and Audit Rotation on Audit Quality - Suwarno, Agus Endro; Anggraini, Yayi Bely; Puspawati, Dewita (Universitas Muhammadiyah Surakarta, 2020)
This study aimed to examine the effect of audit fee, audit tenure, audit rotation and auditor reputation on the audit quality in food and beverage companies listed in Indonesian Stock Exchange of 2014-2018. Population of the research is 90 food an beverage companies listed in Indonesian Stock Exchange of 2014-2018. Sample was taken by using purposive sampling, namely sampling with certain consideration. Based on the criteria, data sample of 104 food and beverage companies for period of three years were obtained, so that sample was 49 data. The data was analyzed by using descriptive statistic analysis and logistic regression analysis. The result shows that audit fee, audit tenure, audit rotation and auditor reputation have no influences to the audit quality.Â Keywords: audit fee, audit tenure, audit rotation, auditor reputation, audit quality